Exploring the squeezed middle: Aucklanders talk about being 'squeezed'. (2nd January 2020) - Curtis, Bruce; Maynard, Angela; Kanade, Nicky
ABSTRACT: This research explores how middle-class Aucklanders, participants in 'the middle', see themselves in terms of being squeezed. It is intended to augment existing statistical based work on class stratification and life chances and facilitate aspects of qualitative research around giving voice. The research confirms the notion of a squeezed middle for the participants based in Auckland, and a striking feature of that confirmation is the centrality of age in demarcating both resourcing (in particular, homeownership versus renting) and narratives. Insofar as the research captures the zeitgeist of the middle, this confirms a neoliberal governmentality wherein a class analysis is interpolated with personal responsibility – and the latter remains paramount. Further, the research demonstrates that empathy is associated with social proximity. The semi-structured interviews also illuminated a widespread sense of resentment. This had two dimensions: directed against neoliberalism as an historic transformation that is seen as the cause of an increasingly squeezed middle, and; against baby boomers. Participants in their 40s demonstrated the highest levels of resentment, and this confirms other research which identifies them as a problematic age cohort because of changing socio-economic conditions.